PENGARUH PENERAPAN METODE MIND MAPPING TERHADAP HASIL BELAJAR IPS KELAS VIII DI SMP N 6 PURWOKERTO - Ristiyani Ristiyani (Soedirman Economics Education Journal, 2019)
This is a True Experiment study by using Posttest Only Control Group Design with the title "The Influence of Mind Mapping Method Implementation on the learning outcomes of Social Science Class in State Junior High School 6 Purwokerto Grade VIII". This study aims to determine the effect of applying the mind mapping method to the learning outcomes of Social Science Class. Population used in this research is grade VIII in SMP N 6 Purwokerto. The sample taken in this research is class VIII D as experimental class with 35 students and class VIII E as control class with 34 students. Besides, the sampling technique used is Cluster Random Sampling. This research shows that there is influence of the application of mind mapping method in the learning outcomes of Social Science Class in grade VII in State Junior High School 6 Purwokerto. The student's achiement using the mind mapping method is higher than using the lecturing method. The results of data analysis using Microsoft Excel and SPSS 16 for windows software shows the average value obtained by the experimental class is 80,2 while the control class is 72,4. Mind mapping learning is proved effective to improve student learning achievement. The influence of mind mapping learning method to learning result is marked by t count > t table that is 3,958 > 1,980 and mean of experiment class value is higher than control class that is 80,2 > 72,4. The implication of this research is to improve the learning result of social science class, the teacher is expected to apply the mind mapping method in IPS learning to improve the learning outcomes and hopefully can provide enough tools and materials for making mind map.